PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Jannah, Miftakul; Hilyana, F. Shoufika; Purwaningrum, Jayanti Putri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
This study was conducted with the aim of determining the effect of using the Contextual Teaching and Learning model in improving students' mathematical problem solving abilities. This research was carried out at SD N 1 Ujungpandan Welahan Jepara with the research subjects of 21 students on the volume of cubes and blocks for the 2022/2023 academic year. The research method used is classroom action research, which is carried out over two cycles, each cycle consisting of three meetings. This study also used data collection techniques of interviews, observations, tests, and documentation. Data analysis of this study used quantitative and qualitative. The results showed that in cycle I, students' mathematical problem-solving ability increased from precycle 38% to 71%. In cycle II, students' mathematical problem-solving ability also increased to 100%. This is because the teacher has related the material according to everyday life so that students are easier to solve the problem of cube and block volume. Thus, the use of the CTL model can improve the mathematical problem solving ability of grade V students of SD N 1 Ujungpandan.